CYBER SECURITY PROBLEMS IN MODERN WORLD - Kotukh , Yevhen (Pressing Problems of Public Administration, 2019)
A pending issue in the present-day research domain is an analysis of the modern trends of cyberspace development, raising awareness as well as elaboration of a complex of priority measures for providing the cyber security in the field of public administration. Globalization and the Internet have stipulated the growth of new opportunities for the public sector to enhance its internal efficiency and better servicing of voters in the e-government format. However, with an increased number of users and a growing role of the Internet in people’s everyday life, digital tools also put the public sector at great risks, thus contributing to the importance of cyber security. Although the demand for e-government (its application) is lagging behind the supply (its availability), governments worldwide persuade voters to use their services, taking advantage of the on-line information benefits. Striving for efficiency and transparency requirements are becoming the driving forces of these processes.To determine the specific features of cyber security in the public sector, it is important to realize the convergence of the following three factors: globalization, the degree of logging on to the Internet, and the trends of providing the public sector services in the Internet, which is normally called ‘e-government’.It is expedient to discern two kinds of cyber threats, namely: 1) politically motivated (for example, cyberwar, cyberterrorism, hacktivism, spying) and non-political threats (for instance, cybercrime, intellectual property theft, fraud, hacking for fun or revenge); 2) those based on potential threats (external or internal). For Ukraine, it is essential to develop typical mechanisms for public administration of information security under the conditions of cyber threats, as well as financial provision of creation, research and trial of information protection systems in the said sphere. The world has had a long history of counteracting cybercrime. Considering the global nature of the threat, it is important to closely cooperate with other countries while developing cyber security measures.